KARAKTERISTIK ANAK PENDERITA HIDROCEPHALUS BERDASARKAN ETIOLOGI, STATUS GIZI DAN UMUR GESTASI DI RSU. HAJI MEDAN 2017 – 2019 - NUGRAHA ILHAMSYAH; ERY SUHAYMI (LP2MTBM MAKARIOZ, 2021)
Hydrocephalus is a build up of cerebrospinal fluid (CSF) in the central nervous system, which is a result of impairedformation, flow and absorption that often affects humans, both infants, children and adults, which can be caused bycongenital abnormalities (malformations), infections, and neoplasms. countries with low and middle income have a largernumber of cases than countries with high income. Hydrocephalus can cause serious problems if left untreated, such asdecreased intellectual abilities and motor deficits. Children with hydrocephalus are most often found in a state of poornutritional status, especially in the group of children with TB meningitis. Knowing the characteristics of children withhydrocephalus who are hospitalized at RSU Haji Medan in 2017-2019. This study was a descriptive study with a crosssectionalretrospective design where the sample data were taken from medical records. Result 57 children withhydrocephalus at RSU Haji Medan was found with the characteristics of the male sex group as many as 33 children (57.9%),the highest age group was Infant (1 month-2 years) as many as 20 children (35.1%), with the etiology of infection in 32children (56.1%), malnutrition status of 31 children (54.4%), history of aterm gestational age totaled 56 children (98.2%),history of VP-Shunt action that was not performed by 28 children (49.1%), and the hydrocephalus type group non-obstructiveas many as 36 children (63.2%). Children suffering from hydrocephalus in RSUP Haji mostly caused by infection with lownutritional status and history of gestational age at term.